Microsoft SQL Server 2012 step by step - Leblanc, Patrick (O'Reilly Media, 2013)
Bibliography: 253 - 283; Teach yourself how to use SQL Server 2012--one step at a time. Ideal for beginning database administrators and developers, this tutorial provides practical, learn-by-doing exercises to help you design and manage databases, develop reports, and employ business intelligence systems